Low-energy D^＊＋D1^0 scattering and the nature of resonance-like structure Z^＋（4430） - 宫明 陈莹 蒙国站 何颂 李刚 刘川 刘玉斌 马建平 孟翔飞 牛志元 沈言 张剑波 张远江 (Chinese physics C, 2010)
Low-energy scattering of D ^＊＋ and D1^0 meson is studied using quenched lattice QCD with improved lattice actions on anisotropic lattices.The threshold scattering parameters,namely the scattering length a 0 and the effective range r 0,for the s-wave scattering in J P = 0 - channel are extracted： a 0 = 2.52（47） fm and r 0 = 0.7（1） fm.It is argued that,albeit the interaction between the two charmed mesons being attractive,it is unlikely that they can form a shallow bound state in this channel.Our calculation provides some useful information on the nature of the newly discovered resonance-like structure Z ＋ （4430） by the Belle Collaboration.